2019
DOI: 10.15537/smj.2019.3.23960
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice on medication error reporting among health practitioners in a tertiary care setting in Saudi Arabia

Abstract: Objectives: To assess knowledge, attitudes and practices towards the reporting of medication errors among health practitioners at King Abdulaziz Medical city in Riyadh, Kingdom of Saudi Arabia. Methods: A cross-sectional study using a self-administered questionnaire was conducted in a convenient sample of 62 physicians and 303 nurses, between June and September 2017 at King Abdulaziz Medical City, Riyadh, Kingdom of Saudi Arabia. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 14 publications
10
38
2
1
Order By: Relevance
“…In particular, nurses reported a higher level of awareness towards IRS than did other specialties, which is in accord with the findings of Alsulami et al, who observed that the nurses demonstrated higher reporting knowledge than did their peers. 5 By contrast, Km, B et al observed that pharmacists had more knowledge of adverse drug reaction (ADR) reporting than did nurses or other specialties. 15 While reviewing the attitude scores, faculty and HCPs did not differ with respect to gender, nationality, age, or working experience.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, nurses reported a higher level of awareness towards IRS than did other specialties, which is in accord with the findings of Alsulami et al, who observed that the nurses demonstrated higher reporting knowledge than did their peers. 5 By contrast, Km, B et al observed that pharmacists had more knowledge of adverse drug reaction (ADR) reporting than did nurses or other specialties. 15 While reviewing the attitude scores, faculty and HCPs did not differ with respect to gender, nationality, age, or working experience.…”
Section: Discussionmentioning
confidence: 97%
“…Especially in the Saudi Arabian context, various researchers have studied the healthcare professionals' knowledge, attitude, and practice towards medical error or adverse drug reactions reporting in Saudi tertiary care hospitals. 5,[7][8][9] A study revealed the barriers, facilitators, strategies, and predictors for adverse drug reactions reporting in three general hospitals in Saudi Arabia. 10 Another study revealed the attitudes of dental professional staff and auxiliaries in Saudi dental institutions over the medical errors' disclosure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] In that context, a paper published by Alsulami et al . revealed that 43.4% of healthcare providers do not have a clear definition of medication errors,[ 25 ] suggesting that patients' knowledge is a continuum of their healthcare providers. Therefore, and starting 2017, the WHO has aimed to reduce the “medication-related errors” to half in 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, few studies have examined the reporting pattern of medication errors among healthcare providers. One study found that 44.8% of healthcare practitioners never reported medication errors [16].…”
Section: Introductionmentioning
confidence: 99%